2015
DOI: 10.14419/gjma.v3i1.3086
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of soret effect on thermohaline convection in dusty ferrofluid saturating a Darcy porous medium

Abstract: The Soret-driven ferro thermoconvective instability of multi-component fluid in a porous medium heated from below and salted from above in the presence of dust particles subjected to a transverse uniform magnetic field has been analyzed using Darcy model for various values of permeability of the porous medium. The salinity effect has been contained in magnetization and density of the ferrofluid. A small thermal perturbation imparted on the basic state and a linear stability analysis is used for this model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Sunil et al [1] reported that for very high values of the magnetic parameter, ferrofluid reacts like a usual fluid while examining the influence of dust particles on ferrofluid in the presence of the magnetic field. Sekar and Raju [2] analyzed the stability of Soret effects on dusty ferrofluid. They reported that the system was considered unstable due to the absorption of the porous media and dust particle parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Sunil et al [1] reported that for very high values of the magnetic parameter, ferrofluid reacts like a usual fluid while examining the influence of dust particles on ferrofluid in the presence of the magnetic field. Sekar and Raju [2] analyzed the stability of Soret effects on dusty ferrofluid. They reported that the system was considered unstable due to the absorption of the porous media and dust particle parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of horizontal magnetic field and rotation of thermohaline convection through porous medium studied by Sharma et al [20], Sunil et al [21], Singh et al [22], Kumar [23] and Abdullah et al [24]. Sekar and Raju [25] studied soret effect on the thermohaline convection in dusty ferrofluid saturating a darcy porous medium, used darcy model and studied linear stability conditions for the onset of stationary and oscillatory convection.…”
Section: Introductionmentioning
confidence: 99%
“…Selvaraj et al [18] investigated convective instability of strongly magnetized ferrofluids. Sekar et al [19] carried out the stability analysis of the Soret effect on thermohaline convection in a dusty ferrofluid saturating a Darcy porous medium.…”
Section: Introductionmentioning
confidence: 99%